Optimization of weed management-systems - the role of ecological models of interplant competition - Kropff, M.J.; Lotz, L.A.P. (Cambridge University Press, 1992)
The strategy to optimize weed management systems with a minimum use of herbicides includes both the adaptation of crop management practices and well designed decision making systems, based on postemergence observations of weed infestations. Both strategies require thorough quantitative insight into the crop weed ecosystem, which can be provided by systems analysis, using process based models. These models also can be applied to similar systems like intercropping. For practical application, however, a simple measure of weed infestation and a simple model which relates weed infestation to yield loss are required. Recent progress in model development is discussed. An alternative empirical model that predicts yield loss from the relative leaf area of the weeds shortly after crop emergence, seems to be a useful approach for prediction of yield loss shortly after crop emergence. The use of systems approaches at different levels of detail for bridging the gap between research and practical application is discussed.